2004
DOI: 10.1161/01.hyp.0000103160.35395.9e
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic Augmentation in Hypertension

Abstract: Abstract-There is growing evidence that essential hypertension is commonly neurogenic and is initiated and sustained by sympathetic nervous system overactivity. Potential mechanisms include increased central sympathetic outflow, altered norepinephrine (NE) neuronal reuptake, diminished arterial baroreflex dampening of sympathetic nerve traffic, and sympathetic neuromodulation by angiotensin II. To address this issue, we used microneurography and radiotracer dilution methodology to measure regional sympathetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
146
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 445 publications
(150 citation statements)
references
References 25 publications
(39 reference statements)
3
146
0
1
Order By: Relevance
“…21,[27][28][29] Many studies have demonstrated that HT volunteers exhibit a reduction in HRV that is associated with a decrease in vagal autonomic modulation and an increase in sympathetic modulation. [30][31][32] Our study demonstrated that untreated HT volunteers presented an increase in HVR that was characterized by an increase in total variance in the RRi compared with NT and HT volunteers treated with Enalapril.…”
Section: Discussionmentioning
confidence: 99%
“…21,[27][28][29] Many studies have demonstrated that HT volunteers exhibit a reduction in HRV that is associated with a decrease in vagal autonomic modulation and an increase in sympathetic modulation. [30][31][32] Our study demonstrated that untreated HT volunteers presented an increase in HVR that was characterized by an increase in total variance in the RRi compared with NT and HT volunteers treated with Enalapril.…”
Section: Discussionmentioning
confidence: 99%
“…35 It might be expected that NET deficiency would result in even greater pressure changes because sympathetic overactivity is recognized as an underlying cause of essential hypertension in humans. 36 However, the NET gene has been absent since embryogenesis, and the nearly normal pressures of resting NET Ϫ/Ϫ mice illustrate developmental adaptation in response to a hyperadrenergic state and the magnitude of sympathetic noradrenergic buffering.…”
Section: Discussionmentioning
confidence: 99%
“…18 High blood pressure is triggered by increased sympathetic influence on the heart and peripheral vessels that leads to hyperkinetic circulation and peripheral vasoconstriction, respectively. [18][19][20] The literature further supports that sympathetic neural factors exert a key role not only in the development and progression of hypertension but also in the pathogenesis of hypertension-related cardiovascular and renal end-organ damage. 18 A number of studies have also examined whether and to what extent sympathetic neural mechanisms participate in two forms of hypertension of recent definition, that is, 'white-coat' and 'masked' hypertension.…”
Section: Mechanisms Involved In Diurnal Blood Pressure Variationsmentioning
confidence: 99%